How to Train Physical Education Teacher to Detect Physical and Social Adaptation Criteria and to Use Them in Education Activity - BYSTRITSKAYA, Elena Vitalyevna (2021)
The problem of primary to secondary school transition is common extremely acute for all teachers. The role of physical education teacher in its solution has several features. One of them is necessity of preserving not only physical health, but also psychological comfort and fixing healthy lifestyle habits. The goal of this article is to determine the health culture forming criteria for primary school pupil and to find the most effective methods of teaching physical education students to use them in school educational process. As a result of research primary school pupil’s health culture components and their functions in adaptation to secondary school process were determined. Also a complex of common and special criteria was presented. This one allows to young physical education teachers to draw individual plans for comfortable adaptation of their pupils to new realities of educational process in secondary school.